Many a little makes a mickle: Macro portfolio stress test for small and medium-sized German banks - Ramona Busch; Philipp Koziol; Marc Mitrovic (Deutsche Bundesbank, 2015)
We develop a macroeconomic portfolio stress test that is specifically geared towards small and medium-sized banks. We combine a credit risk stress test which simulates credit impairments via a CreditMetrics type multi-factor portfolio model with an income stress test in the form of dynamic panel data regressions. Based on a stress scenario that extends experience of the financial crisis by integrating the current low interest rate environment, we analyse the stress impact on banks' capital ratios. Our results show that savings banks and cooperative banks prove to be very resilient to macroeconomic stress, while more than 6% of our sample's credit banks "fail" the stress test, mainly due to their lack of capital. The main stress drivers prove to be credit impairments rather than other net income components.
Keywords: C13; C15; G21; G33; 330; Macro Stress Tests; Macroprudential Supervision; Small and Medium-sized Banks; Income Stress Test; Credit Risk